Comparing Contributions of Passive and Active Tick Collection Methods to Determine Establishment of Ticks of Public Health Concern Within Illinois. Issue 4 (15th April 2021) - Lyons, Lee Ann; Brand, Mary E; Gronemeyer, Peg; Mateus-Pinilla, Nohra; Ruiz, Marilyn O'Hara; Stone, Chris M; Tuten, Holly C; Smith, Rebecca L
Abstract: In Illinois, between 1990 and 2017, tick-borne diseases in humans increased 10-fold, yet we have insufficient information on when and where people are exposed to vector ticks (Ixodida: Ixodidae). The aims of our research were to compare contributions of passive and active tick collection methods in determining establishment of ticks of public health concern and obtain information on tick distributions within Illinois. We used three surveillance strategies within the Illinois Tick Inventory Collaboration Network to gather information about the ticks of public health concern: 1) passive collection (voluntary submission by the public); 2) systematic collection (biweekly active surveillance); and 3) special collections (active collections in locations of special interest). Of collected adult and nymphal ticks, 436 were from passive collections, 142 from systematic collections, and 1, 270 from special collections. Tick species distribution status changed in 36 counties. Our data provide noteworthy updates to distribution maps for use by public health agencies to develop prevention and control strategies. Additionally, the program built a network of collaborations and partnerships to support future tick surveillance efforts within Illinois and highlighted how the combination of the three surveillance strategies can be used to determine geographic spread of ticks, pinpoint locations in need of more surveillance, and help with long-term efforts that support phenology studies.